A Musicalidade do Bumba-Boi da ilha: construção de instrumental artístico e pedagógico. - LEITÃO, Rogério Ribeiro das Chagas (2018)
The present work deals with the musical rhythm analysis of the “Bumba-Boi da Ilha”, cultural expression present in the State of Maranhão. The survey was developed in communities where are located the groups that develop this manifestation of popular culture. Later, the results have been applied in the context of the drums classroom of the school of music of Maranhão Lilah Lisboa (EMEM), through the transcripts of rhythmic material collected, connected to a specific repertoire of this musicality present in the urban song of Maranhão. This analysis is presented from the point of view do ethnomusicological, articulated with the field of music education and with the embedded narrative with the parameters of the "new cultural history". Field research has played important tool on observation, data collection and analysis. The research methodology adopted is based on qualitative research, through participant observation, depoiments and interviews open applied to categories of notability to work. In part dedicated to transcriptions and musical applications we use the methodology named "play along". It's a work that articulates the traditional and popular music from Maranhão, in order to provide educational material for analysis of the “Bumba-Boi da Ilha” and your consequent artistic and pedagogical application.